Infrastructural mechanisms leading toward pro-accountable care organisation orientation: a survey of hospital managers. (1st January 2014) - Wan, Thomas T.H.; Masri, Maysoun Dimachkie; Ortiz, Judith
Organisations across the country are transforming the way they deliver care, in ways similar to the accountable care organisation (ACO) model supported by Medicare. ACOs modalities are varying in size, type, and financing structure. Little is known about how specific infrastructural mechanisms influence hospital managers' pro-ACO orientation. Using an electronic-survey of hospital managers, this study explores how pro-ACO orientation, as a latent construct, is captured from the perceptions of hospital managers; and identify infrastructural mechanisms leading to the formation of pro-ACO orientation. Of the total hospital respondents, 58% are moving toward the establishment of ACOs; 56% are planning to join in the next two years; 48% are considering joining ACOs; while 25% had already participated in ACOs during 2012. Urban hospitals are more likely than rural hospitals to be engaged in ACO development. The health provider network size is one of the strongest indicators in predicting pro-ACO orientation.